2013
DOI: 10.1021/bm400204y
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Core–Shell Architecture of Hemoglobin and Human Serum Albumin as an Artificial O2 Carrier

Abstract: Covalent core-shell structured protein clusters of hemoglobin (Hb) and human serum albumin (HSA) (HbX-HSAm) (m = 2, 3) with novel physiological properties were generated by linkage of Hb surface lysins to HSA cysteine-34 via an α-succinimidyl-ε-maleimide cross-linker (X: 1 or 2). The isoelectric points of HbX-HSAm (pI = 5.0-5.2) were markedly lower than that of Hb and almost identical to that of HSA. AFM and TEM measurements revealed a triangular Hb1-HSA3 cluster in aqueous medium. The complete 3D structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 49 publications
2
100
0
Order By: Relevance
“…In another recent nanotechnology approach, core-shell cluster structures were formed by conjugating human serum albumin (HSA) on Hb using Hb surface lysines conjugated to HSA cysteine-34 using α-succinimidyl-ε-maleimide cross-linker. 77 These Hb-HSA clusters are envisaged to have low risks of rapid clearance and extravasation, and high circulation stability. A further modification of these Hb-HSA core-shell nanoclusters was recently reported where anti-oxidant enzymes and platinum nanoparticles were embedded in the HAS pockets for protection of Hb.…”
Section: B Rbc Substitutes and Oxygen Carrier Systemsmentioning
confidence: 99%
“…In another recent nanotechnology approach, core-shell cluster structures were formed by conjugating human serum albumin (HSA) on Hb using Hb surface lysines conjugated to HSA cysteine-34 using α-succinimidyl-ε-maleimide cross-linker. 77 These Hb-HSA clusters are envisaged to have low risks of rapid clearance and extravasation, and high circulation stability. A further modification of these Hb-HSA core-shell nanoclusters was recently reported where anti-oxidant enzymes and platinum nanoparticles were embedded in the HAS pockets for protection of Hb.…”
Section: B Rbc Substitutes and Oxygen Carrier Systemsmentioning
confidence: 99%
“…Komatsu et al recently developed a novel type of acellular HBOCs, referred to as Hb–albumin clusters [88]. The Hb–albumin cluster is composed of one Hb in the center and three or four human serum albumins (HSA) in the periphery, and was prepared by a covalent linkage between the Cys34 residue of HSA and the surface Lys amino groups of Hb via a heterobifunctional cross-linker.…”
Section: Newer Generated Acellular Type Hbocsmentioning
confidence: 99%
“…Particularly, Lys-82( β ) plays a crucially important role in controlling the quaternary structure deformation from the Relaxed state to a Tense state. We reported previously that Lys-82( β ) is a binding partner of Cys-34 of HSA based on the 3D reconstruction of Hb-HSA 3 28. Therefore, it can be concluded that (i) the capping of Cys-93( β ) elevates the O 2 affinity and (ii) modification of surface Lys groups interferes with the Hb quaternary transition, resulting in the decline of O 2 -binding cooperativity.…”
Section: Resultsmentioning
confidence: 94%
“…We have recently synthesized a covalent core–shell structured protein cluster comprising a bovine Hb in the center and human serum albumins (HSAs) at the periphery, hemoglobin–albumin cluster (Hb-HSA 3 ), as a unique artificial O 2 -carrier28293031. The Hb nucleus is wrapped covalently with HSA.…”
mentioning
confidence: 99%